2007
DOI: 10.1177/1352458506070319
|View full text |Cite
|
Sign up to set email alerts
|

The clinical response to minocycline in multiple sclerosis is accompanied by beneficial immune changes: a pilot study

Abstract: Minocycline has immunomodulatory and neuroprotective activities in vitro and in an animal model of multiple sclerosis (MS). We have previously reported that minocycline decreased gadolinium-enhancing activity over six months in a small trial of patients with active relapsing-remitting MS (RRMS). Here we report the impact of oral minocycline on clinical and magnetic resonance imaging (MRI) outcomes and serum immune molecules in this cohort over 24 months of open-label minocycline treatment. Despite a moderately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 33 publications
4
69
0
1
Order By: Relevance
“…[91][92][93] In addition, minocycline was found to reduce relapse rate and gadolinium-enhancing magnetic resonance imaging lesions in a pilot trial in relapsing-remitting MS patients. 94,95 These results are encouraging. Although it is tempting to state that the effectiveness of minocycline in MS is related to its MMP inhibitory actions, it is important to point out that minocycline possesses a multitude of immunomodulatory and anti-apoptosis functions 96 so that its potential usefulness in MS may even be unrelated to its MMP inhibitory activity.…”
Section: Figsupporting
confidence: 69%
“…[91][92][93] In addition, minocycline was found to reduce relapse rate and gadolinium-enhancing magnetic resonance imaging lesions in a pilot trial in relapsing-remitting MS patients. 94,95 These results are encouraging. Although it is tempting to state that the effectiveness of minocycline in MS is related to its MMP inhibitory actions, it is important to point out that minocycline possesses a multitude of immunomodulatory and anti-apoptosis functions 96 so that its potential usefulness in MS may even be unrelated to its MMP inhibitory activity.…”
Section: Figsupporting
confidence: 69%
“…This tetracycline antibiotic that inhibits MMP activity and reduces the severity of animals immunized for EAE (22)(23)(24) has shown promise in relapsing-remitting MS in early clinical trials (25)(26)(27)(28) and, more recently, was found to be effective in a phase III trial in early MS (L. M. Metz et al, submitted for publication). We find that both murine and human T cells were reduced in the expression level (MFI) of EMMPRIN by minocycline, as well as in the percentage of T cells with EMMPRIN expression.…”
Section: Discussionmentioning
confidence: 99%
“…We focus on the potential MS medication minocycline, a tetracycline antibiotic that inhibits MMP activity (21) and reduces the severity of animals immunized for EAE (22)(23)(24). From these animal studies, minocycline was tested and found to have promise in relapsing-remitting MS as suggested by early clinical trials (25)(26)(27)(28). More recently, a phase III trial in patients with a first demyelinating event (clinically isolated syndrome) found that minocycline reduced the acquisition of a second event to become clinically definite MS (L. M. Metz, D. K. B. Li, A. Traboulsee, P. Duquette, M. Eliasziw, G. Cerchiaro, J. Greenfield, A. Riddehough, M. Yeung, M. Kremenchutzky, et al, submitted for publication).…”
mentioning
confidence: 99%
“…These include anti-oxidant [1], anti-apoptotic [2], anti-metastatic [3] and most notably anti-inflammatory effects [2,[4][5][6]. Tetracyclines are inexpensive, have a very good safety profile and have been investigated in the treatment of a number of inflammatory diseases including rheumatoid arthritis [6,7], periodontitis [8], cardiac ischaemia-reperfusion injury [9] and a wide range of central nervous system pathologies including Parkinson's disease [10], multiple sclerosis [11], amylotrophic sclerosis [12,13], and both global and focal cerebral ischaemia [4,5].…”
Section: Introductionmentioning
confidence: 99%